The Implementation of VCR Technique in Teaching Explanation Text for the Eleventh Grade Students of SMAN 1 Labuhan Haji in the School Year 2021/2022 - Saiful Bahri (Literasi: Jurnal Pendidikan Guru Indonesia, 2023)
This study is intended to find out the implementation of the VCR technique in teaching explanatory texts to eleventh grade students of SMAN 1 Labuhan Haji in the school year 2021/2022. This study was classroom action research (CAR) which is implemented in four cycles, each cycle consists of four activities, and they are planning, action, observation, and reflection. The subject of the study was the eleventh grade students of SMAN 1 Labuhan Haji, which consists of 30 students (10 males and 20 females). To collect the data the present researcher used multiple choice test and essay test to get the quantitative data and observation sheets to get the qualitative data. The conclusion of this study is that in each cycle of student completeness there is an increase even though the increase is not very significant, because it does not reach the classical completeness that has been determined previously, namely if KK ≥ 80% means that class XI MIPA 1 students who get a minimum KKM score of 75 have reached 80% or more, means complete learning. With KK (classical completeness) which reached 83.33% in cycle IV, thus answering the previously formulated action hypothesis, namely that the application of the VCR technique can increase the ability of Class XI MIPA 1 Students of SMAN 1 Labuhan Haji in the school year 2021/2022 in explanation text learning.